INFLUENCE USE OF MOBILE BANKING AGAINST SATISFACTION GENERATIONS OF CUSTOMERS MILLENNIALS AT BANK SYARIAH INDONESIA (BSI) - Ratnasari; Reta Lu'lu Ul Fauziah; Alaya, Viola (Program Studi Manajemen Keuangan Syariah IAIN Parepare, 2023)
Study This aim for analyze satisfaction generations of customers millennials in Indonesian Islamic banks (BSI). Study This use approach quantitative with survey method. Questionnaire has given to public general. Collected data analyzed use method statistics descriptive and inferential. Study This have objective for know How influence use of mobile banking against satisfaction generations of customers millennials at Bank Syariah Indonesia (BSI). Research results show that influence use of mobile banking against satisfaction generations of customers millennials give impact positive and significant against interest save customers at Bank Syariah Indonesia (BSI) and own level moderate relationship meaning, no too strong and not too weak, however significant between satisfaction customers millennials on the use of mobile banking at BSI bank.